The most fundamental and popular literature on functional near-infrared spectroscopy: a bibliometric analysis of the top 100 most cited articles - Li, Jiyang; Li, Yang; Huang, Maomao; Li, Dan; Wan, Tenggang; Sun, Fuhua; Zeng, Qiu; Xu, Fangyuan; Wang, Jianxiong (Frontiers in Neurology, 2024)
Background: Functional near infrared spectroscopy (fNIRS) has developed rapidly in recent years, and there are more and more studies on fNIRS. At present, there is no bibliometric analysis of the top 100 most cited articles on fNIRS research. Objective: To identify the top 100 most cited articles on fNIRS and analyze those most fundamental and popular articles through bibliometric research methods. Methods: The literature on fNIRS of web of science from 1990 to 2023 was searched and the top 100 most cited articles were identified by citations. Use the bibliometrix package in R studio and VOSviewer for data analysis and plotting to obtain the output characteristics and citation status of these 100 most cited articles, and analyze research trends in this field through keywords.Results: A total of 9,424 articles were retrieved from web of science since 1990. The average citation number of the 100 articles was 457.4 (range from 260 to 1,366).University had the largest number of top 100 papers. Harvard University (n=22) conducted most cited articles. The United States, Germany, Japan, and the United Kingdom had most cited articles respectively. The most common keywords were